Pengaruh Self-efficacy Technology, Risk Technology, dan Pemahaman Perpajakan terhadap Minat Menggunakan E-filing : Studi Kasus pada Wajib Pajak Orang Pribadi KPP Pratama Makassar Utara - Agus Bandang; Patricia Yuliani Mambela; Nirwana Nirwana; Haerial Haerial (Al-Buhuts, 2025)
This research aims to analyze the influence of self-efficacy technology, risk technology, and tax understanding on the interest in using e-filing among Individual Taxpayers at KPP Pratama Makassar Utara. The method used is a survey with a questionnaire in the form of a Google form distributed to 135 respondents registered as Taxpayers at KPP Makassar Utara. The analysis results show that technology self-efficacy has a positive and significant effect on the interest in using e-filing, meaning that the higher the taxpayer's confidence in their ability to use technology, the greater their interest in using e-filing. Although technology risk shows a positive influence, its impact is not significant, indicating that concerns about data security do not significantly hinder the use of e-filing. Additionally, tax understanding also has a positive and significant effect on the interest in using e-filing, emphasizing the importance of having a good understanding of tax procedures in encouraging the adoption of this technology. These findings provide insights for the Directorate General of Taxes to design educational and training strategies that can enhance taxpayers' interest in using e-filing.